Frictions in Shadow Banking: Evidence from the Lending Behavior of Money Market Mutual Funds - Chernenko, Sergey; Sunderam, Adi (Review of Financial Studies, 2014)
We document frictions in money market mutual fund lending that lead to the transmission of distress across borrowers. Using novel security-level holdings data, we show that funds exposed to Eurozone banks suffered large outflows in mid-2011. These outflows had significant spillovers: non-European issuers relying on such funds raised less short-term debt financing. Issuer characteristics do not explain the results: holding fixed the issuer, funds with higher Eurozone exposure cut lending more. Due to credit market frictions, funds with low Eurozone exposure provided substitute financing only to issuers they had pre-existing relationships with, even though issuers are large, highly rated firms.